Perjanjian Kerja Waktu Tertentu (PKWT) Pada PT. Angkasa Pura Suport Badung - Ni Luh Putu Emi Sukasih; Anak Agung Laksmi Dewi; Desak Gde Dwi Arini (Fakultas Hukum, Universitas Warmadewa, 2021)
The ongoing development of globalization will have a direct or indirect impact on the existence of workers, one of which is in terms of the quality of production and labor procedures. This study aims to examine the arrangement of a certain time work agreement (PKWT) at PT. Angkasa Pura Support Badung and revealed the legal consequences of violating a certain time work agreement (PKWT) on the rights and obligations of PT. Angkasa Pura Support Badung. The research method uses normative legal research and a problem approach, namely the legislation approach and the conceptual approach. The legal materials used are primary and secondary legal materials collected through documentation and recording methods. Furthermore, the data is processed and analyzed by qualitative descriptive. The results showed that the arrangement of a certain time work agreement (PKWT) at PT. Angkasa Pura Support Badung is made using a standard form of agreement, so it must comply with the provisions of the legislation which is the main requirement for the validity of an agreement and is also the legal basis of a work agreement for a certain time. The legal consequences of violating a certain time work agreement (PKWT) on the rights and obligations of PT. Angkasa Pura Support Badung is subject to sanctions in the form of a warning, a warning letter (SP), and suspension and finally layoffs occur.